Multifunctional ENY2 Protein Interacts with RNA Helicase MLE. - Nikolenko, J.V.; Kurshakova, M.M.; Krasnov, A.N. (Doklady. Biochemistry and Biophysics, 2019)
ENY2 protein of Drosophila melanogaster was previously discovered and characterized in our laboratory [1, 2]. It was found that ENY2 is a subunit of several multiprotein complexes and connects various stages of gene expression [3-5]. This work is devoted to studying the interaction of ENY2 with RNA helicase MLE. This interaction was confirmed by independent methods. Data indicating that this interaction is conserved in evolution and is important for the functioning of MLE in both sexes were obtained.